Analisis Tarikan dan Bangkitan Perjalanan Akibat Pembangunan Mix-Used Plan (Mix-used JogjaOne Park) dengan Metode Pembanding - Muchlisin, Muchlisin (Universitas Muhammadiyah Yogyakarta, 2016)
Developing an hotel, apartment, condotel, housing, malls and plazas often happens in various corners of the Yogyakarta region. This fact is also triggered increasingly high demand for housing in the city (city living) which is adjacent to the location of work, study or daily activities or in this case is a mix-used planning called Mix-Used JogjaOne Park (JOP). This study aims to determine the magnitude of the impact of traffic on the trip generation and attraction caused Mix-Used JogjaOne Park (JOP) either on the existing condition or when operational in 2020 and 2025. The method used to predict the method of traffic generation using a comparison against similar activities. For comparative exercise activity, is used as a comparison Ambarukmo Plaza mall and shopping activities. While Mataram City as a comparison of activities and hotel apartments. Indonesian Highway Capacity Manual 1997 is used to determine the performance analysis of the road network. From the analysis conducted, the performance conditions on Jalan Adi Sucipto still at LOS D (DS 0.9) on the existing conditions, while at operaisonal at LOS E (DS 1). The condition is not signalized intersection Babarsari - Jl. Adi Sucipto at LOS B (average delay of 5.1 to 15 sec / veh) on condition eksiting, while the LOS still operational at the signalized intersection LOS B. In the East Ringroad - Jl. Adi Sucipto at LOS F (delay (sec / veh) 60) on condition eksting, while also operating at LOS F. And at three signalized intersections Janti Fly Over at LOS D (delay average is 25.1 to 40 seconds / veh) on condition eksting, whereas when operating at LOS E ((delay average is 40.1 to 60 sec / veh).